2021
DOI: 10.1371/journal.pone.0251916
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 inhibitors may improve the mortality of coronavirus disease 2019: A meta-analysis

Abstract: Aims DPP-4 inhibitors are predicted to exert a protective effect on the progression of coronavirus disease 2019 (COVID-19). We conducted this meta-analysis to investigate this hypothesis. Methods Four databases, namely, PubMed, Web of Science, EMBASE and the Cochrane Library, were used to identify studies on DPP-4 and COVID-19. The outcome indicators were the mortality of COVID-19. Funnel plots, Begg’s tests and Egger’s tests were used to assess publication bias. Results Four articles were included with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 35 publications
2
41
0
1
Order By: Relevance
“… 47 Therefore, continued administration of DPP4 inhibitors, commonly used in people with diabetes, has been discussed in patients infected with SARS-CoV-2. 48 , 49 Although a retrospective analysis showed that DPP4 inhibitors can improve mortality in patients with COVID-19 and type 2 diabetes, 50 an open-label, prospective, multicenter, randomised clinical trial in three Israeli hospitals found no differences in the time to clinical improvement between hospitalised patients with diabetes and COVID-19 who received linagliptin and a control group receiving standard of care. 51 …”
Section: Sex Differences In Covid-19mentioning
confidence: 99%
“… 47 Therefore, continued administration of DPP4 inhibitors, commonly used in people with diabetes, has been discussed in patients infected with SARS-CoV-2. 48 , 49 Although a retrospective analysis showed that DPP4 inhibitors can improve mortality in patients with COVID-19 and type 2 diabetes, 50 an open-label, prospective, multicenter, randomised clinical trial in three Israeli hospitals found no differences in the time to clinical improvement between hospitalised patients with diabetes and COVID-19 who received linagliptin and a control group receiving standard of care. 51 …”
Section: Sex Differences In Covid-19mentioning
confidence: 99%
“…Taken together, these findings indicate that GLP-1 could be a novel therapeutic method for the treatment of PH. Recently, a meta-analysis showed that DPP4 inhibitors may improve mortality in COVID-19 disease [ 62 ]. The pathogenesis of COVID-19 is known to involve not only viral infection of tracheal and alveolar epithelial cells but also pulmonary ECs.…”
Section: Inflammation-mediated Endomtmentioning
confidence: 99%
“…Although decreased mortality and respiratory complications were also found among similar studies, Patoulias et al and Yang et al showed no significant results possibly due to small sample size [28][29][30][31][32][33] . Study that were conducted by Patoulias et al also showed a difference between J o u r n a l P r e -p r o o f inpatient and outpatient settings in which inpatient setting is associated with significant effect of reduced mortality (RR, 0.50; 95% CI, 0.34 to 0.71; I2=0%; P=0.0001) while the latter showed no significant effect (RR, 1.14; 95% CI, 0.78 to 1.66; I2=81%; P=0.50) 28 .…”
Section: Discussionmentioning
confidence: 90%